Prenatal alcohol exposure: An assessment strategy for the legal context. (September 2015) - Brown, Natalie Novick; Burd, Larry; Grant, Therese; Edwards, William; Adler, Richard; Streissguth, Ann
Abstract: Studies over the last two decades have shown that people with fetal alcohol spectrum disorders (FASD) have the kind of brain damage that increases risk of criminal behavior. Thus, it is generally accepted that FASD is likely to affect a sizable minority of individuals involved in the justice system. Most of these defendants have never been diagnosed because they lack the facial abnormalities and severe intellectual deficiency that would have improved identification and diagnosis in childhood. Despite the fact that an FASD diagnosis and associated cognitive deficits may be directly relevant to offense conduct and post-arrest capacities, screening for prenatal alcohol exposure (PAE) by legal teams remains relatively rare. This article addresses the relatively straightforward screening process with strategies that may be used singly or in combination to produce information that can establish PAE and provide a foundation for diagnostic assessment by medical and mental health experts.